Covid-19 Impacts on the Forest Sector in Countries in the Western Balkans - United Nations Economic Commission for Europe (United Nations, 2021)
This report summarizes the impacts of the COVID-19 pandemic on the forest sector of countries in the Western Balkans (WB) (Albania, Bosnia and Herzegovina, Montenegro, North Macedonia and Serbia) during the first three quarters of 2020. It focuses on production, export, import, consumption, prices and employment of the main wood products: roundwood, sawnwood, wood-based panels, wooden furniture, paper and paperboards. It also covers recovery measures implemented by Western Balkan governments. This report employs economic indicators for the period January-September 2020, alongside data from various sources, such as official statistics, international data bases (COMTRADE, EUROSTAT, FAO, UNECE), domestic organizations, as well as interviews with forest products companies of all sizes, which were used for their views on the impact of COVID-19.